Gozd v Valvasorjevi Slavi vojvodine kranjske - Hrast, Špela (Acta silvae et ligni, 2017)
Forest is connected with numerous roles and functions, which can vary through time and place, thereby bearing the important information on the individual and social perception and attitudes toward forest. We have analysed Valvasor%s identification of forest roles and functions through content analysis of the Glory of the Duchy of Carniola. Eleven of the seventeen different forest functions can be recognized, which shows the author%s broad perception of the forest. Valvasor can also be praised for his exceptional identification of the diversity of Carniola forests. We can identify 25 different woody plants with the most frequently mentioned species belonging to the beech, pine, oak, chestnut and fir genera. Altogether, 78 different species or groups of forest animals are mentioned. Valvasor gives less importance to invertebrates than vertebrates, whereby not all vertebrates are equally important to him, assigning more importance to birds and mammals connected with hunting or beautiful singing.
Keywords: ecosystem services; ekosistemske storitve; species diversity; vrstna pestrost; funkcije gozdov; forest functions; forest roles; vloge gozdov; Slava vojvodine Kranjske; The Glory of the Duchy of Carniola